Cystic duodenal dystrophy. Typical case as an example of diagnosticsand surgical tactics - V. I. Yegorov; V. A. Koubyshkin; G. G. Karmazanovsky; A. I. Schegolev; N. I. Yashina; Yu. A. Stepanova; Ye. N. Solodinina; N. S. Izmailova (Бюллетень сибирской медицины, 2007)
Duodenal dystrophy, a chronic inflammation of the aberrant pancreatic tissue in the duodenal wall, is a relatively rare disease in the practice of physicians. The heterotopic pancreas is usually functioning, and the development of acute and chronic pancreatitis in it is even more probable than in the orthotopic gland as a result of an underdeveloped duct system. The progression of ectopic pancreatitis associated with increasing cystic formation could lead to a blockade of the major or minor duodenal papilla and subsequent chronic pancreatitits in the pancreas proper. Furthermore, a malignant transformation of the aberrant pancreas is not a rare occurrence. It is essential to carry out a timely and sharp diagnosis of this condition as it often defines the surgical tactics. The purpose of this report is to present a typical case of cystic duodenal dystrophy.